2014
DOI: 10.5455/njppp.2014.4.130620131
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestation of HIV infection in North-Eastern part of India

Abstract: Background: The nervous system is among the most frequent and serious target of HIV infection, occurring in patients with profound immunosuppression even some time neurological disease is the first manifestation of symptomatic HIV infection in 10-20% of patients. Aims & Objective: (1) To study the clinical, investigation profile and various neurological disorders in HIV positive patients; (2) To correlate neurological manifestations in HIV patients with CD4 Counts. Materials and Methods: 40 HIV positive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 13 publications
3
14
0
Order By: Relevance
“…10 Shri Ram Sharma et al also found an incidence of 5.49% of CVA in their study. 16 In our study DSPN (13.3%) was the most common primary neurological illness followed by CIDP (6.7%), which is comparable with the study from NIMS 8 in which DSPN (3.13%) was more common than CIDP (1.83%). In our study, we found only 1 patient (2.2%) with CNS lymphoma, which can be compared with other study.…”
Section: Symptomssupporting
confidence: 89%
See 1 more Smart Citation
“…10 Shri Ram Sharma et al also found an incidence of 5.49% of CVA in their study. 16 In our study DSPN (13.3%) was the most common primary neurological illness followed by CIDP (6.7%), which is comparable with the study from NIMS 8 in which DSPN (3.13%) was more common than CIDP (1.83%). In our study, we found only 1 patient (2.2%) with CNS lymphoma, which can be compared with other study.…”
Section: Symptomssupporting
confidence: 89%
“…This finding is in concordance with many other studies. In a study from NEIGRIHMS, Shillong, Shri Ram Sharma et al 16 found Tuberculous meningitis (43.95%) to be more common than cryptococcal meningitis (14.2%) followed by toxoplasmosis (2.19%). Similarly, Himanshu M Rana et al 15 found tuberculous meningitis (34%) more common than Cryptococcal meningitis (14%) and cerebral toxoplasmosis (10%).…”
Section: Symptomsmentioning
confidence: 98%
“…Our results are comparable to RANA et al who observed neck rigidity in 76% of TBM and 57% cryptococcal meningitis [11] and Sharma et al who observed that signs of meningeal irritation were present in 50% of the cases. [10] Gait abnormalities were found in 9 (17.54%) out of 57 patients of neurological manifestation, which included spastic 5.26% (3 out if 57) and hemiplegic 10.53% ( 6 out of 57) gaits. Sharma at al observed gait abnormalities in 10% patients 4 had ataxia of which 2 patients had cerebellar ataxia and the other 2 had sensory ataxia.…”
Section: Symptom Present Studymentioning
confidence: 98%
“…Satyendra et al [12] Sharma et al [10] Patel et al [6] Atill et al [9] Sircar at al [22] Headache Atill at al found papilledema in 35.08% [9] sharma et al observed papilledema 3 out of 40 patients (7.5%). [10] Meningeal signs were documented only in 25 out of 57 patients with neurological manifestation (43.86%). Only 62.96% (17 put of 27) of TBM and 62.50% (5 out of 8) of Cryptococcal meningitis had neck rigidity.…”
Section: Symptom Present Studymentioning
confidence: 99%
“…in Sub-Saharan Africa [3,4]. Though once known to be rare, cryptococcosis has occurred at a high frequency in India in the past two decades [5,6].Furthermore, prevalence of HIV-associated CM is also found to be common in many parts of India including North-eastern and as well as in Southern India [7,8].Cryptococcal meningitis is the fourth most commonly recognized cause of life-threatening infection among AIDS patients [9].Despite availability of antiretroviral therapy, the rise in rate of infections due to HIV/AIDS, suppress the cell mediated immune system and subjects are predisposed for opportunistic infections. Additionally, In AIDS patients, it is characterized by lack of meningeal signs and diminished inflammatory response [10].…”
Section: Introductionmentioning
confidence: 99%